Chromolaena odorata L. Leaf Extract Elevates Cytotoxicity of Doxorubicin on 4T1 Breast Cancer Cells - Putri, Amaliya Permata; Rahmawati, Desty Restia; Rahman, Faaza Aulia; Meiyanto, Edy; Ikawati, Muthi (Indonesian Journal of Cancer Chemoprevention, 2023)
Chemotherapeutic agents for breast cancer such as doxorubicin can attack normal cells as the side effects. Chromolaena odorata L. and its chemical content, sinensetin, have potential anticancer  and  antioxidant  properties.  The  objective  of  this  research  is  to  examine  the anticancer properties of C. odorata leaves extract and sinensetin on 4T1 triple negative breast cancer (TNBC) cells combined with doxorubicin. The MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5 diphenyltetrazolium  bromide)  assay  on  4T1  cells  was  used  to  determine  the  IC50 and the Combination  Index  (CI)  of  the  two  agents  in  combination.  Washing  out the  treatment  and determining  the  cells  viability  after  a  few  days  was done  to evaluate  the  persistence  of the  effects  to  cancer  cells.  Chromolaena odorata  extract  (COE)  obtained  was  proven  to contain  sinensetin  which  gave  a positive  signal  on  the  chromatogram.  COE  and  sinensetin were  moderately  cytotoxic  to  4T1  cells  with  IC50  value  of  53  μg/mL  and  58  μM  (21.6 μg/mL), respectively. Both compounds were synergist (CI<0.7) to strong synergist (CI<0.3) when combined with doxorubicin (IC50 90 nM = 0.05 μg/mL). COE and sinensetin exhibited moderate and not cytotoxic against Vero cells with IC50 values of 60 μg/mL and 243 μM (90.43 μg/mL), respectively. Both COE and sinensetin showed selectivity index values of >1 (1.13 and 4.19, respectively).  Moreover,  the  cytotoxic  effects  of  COE  on  4T1  cells  was  persisted  until  48  h after  removing  COE  from  the  medium,  indicating  the  tumor-suppression  potency  of  COE. Our findings strengthen the scientific basis of C. odorata leaves extract to be developed as a co-chemotherapeutics agent for doxorubicin on TNBC.Keywords: Chromolaena odorata L., breast cancer cells, doxorubicin, co-chemotherapy, kidney cells.